Battery, preparation method thereof and electric equipment
By using sulfur-doped active materials in lithium-ion batteries and electrolytes with carbonate-based compounds and lithium salts in the charging process, a solid electrolyte with high ionic conductivity is generated, which solves the problem of poor contact between the electrode-electrolyte interface and improves the improvement of the electrolyte interface. The battery's rate and safety performance are achieved.
Patent Information
- Application Number
- CN202411168850.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-13
AI Technical Summary
When existing solid-state lithium-ion batteries prepare solid electrolytes and positive and negative electrode materials in an in situ manner, they lead to poor interface contact between electrodes and electrolytes, large interface resistance, and ion mass transfer, which affects the rate performance, and polymerized monomers and initiators. Residual affects battery performance.
The sulfur-doped active material is used as the negative electrode active material, and the electrolyte of carbonate-based compounds and lithium salts is combined to form a solid electrolyte with high ionic conductivity during the charging process, forming an electrode-electrolyte interface with low interface resistance. .
The battery's high safety performance and good rate performance are achieved, while avoiding the negative impact of polymer monomer/initiator residue on battery performance.
Smart Images

Figure CN119133609A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a battery and a preparation method thereof, and electrical equipment. Background Art
[0002] As an important device for energy storage, lithium-ion batteries have high energy and power density, excellent recyclability and reliability, and have been widely used in various fields of daily life. However, with the rapid growth of demand for electric vehicles, a new generation of lithium-ion batteries with higher energy density, longer cycle life and faster charging rate has been gradually developed. However, the safety performance of batteries cannot be ignored. Currently, commercial lithium-ion batteries mainly use liquid electrolytes, which have poor thermal stability, volatility and flammability. To address this problem, semi-solid batteries / all-solid batteries using solid electrolytes have gradually come into people's view and become an important development direction.
[0003] The current preparation method of solid-state batteries includes: first synthesizing oxide solid electrolyte, sulfide solid electrolyte or polymer solid electrolyte material, and then compounding it with positive electrode sheet / negative electrode sheet / diaphragm by non-in-situ methods such as slurry coating or pressurization. A small amount of liquid electrolyte (generally not more than 15wt%) can be added to assemble a semi-solid battery. However, no matter what kind of solid electrolyte material is used, compounding with positive and negative electrode materials by non-in-situ methods will lead to poor electrode-electrolyte interface contact, large interface resistance, small contact area, ion mass transfer is hindered, and rate performance is poor. Someone proposed to prepare the solid electrolyte layer by in-situ polymerization to solve the problem of poor electrode-electrolyte interface contact, that is, adding initiator and polymerization monomer to the liquid electrolyte, and after infiltration with the electrode, the polymerization monomer will be induced to undergo in-situ polymerization reaction under heating / light conditions, and the polymer solid electrolyte is filled on the surface and pores of the porous electrode to form an electrode-electrolyte interface. However, the ionic conductivity of this in-situ generated polymer electrolyte is low, and the initiator and polymerization monomer will have a certain degree of residue in the system, affecting the interface and battery performance. Summary of the invention
[0004] The present application provides a battery and a preparation method thereof, and an electrical device, which have good electrode-electrolyte interface contact and good rate performance.
[0005] In a first aspect, the present application provides a battery, comprising a negative electrode plate and an electrolyte, wherein the negative electrode plate is at least partially immersed in the electrolyte; the negative electrode plate comprises a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer is attached to the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a sulfur-doped active material; the electrolyte comprises a carbonate-based compound and a lithium salt.
[0006] As an optional implementation, the sulfur loading of the sulfur-doped active material is 1% to 20% by mass.
[0007] As an optional embodiment, the sulfur-doped active material includes at least one of sulfur-doped graphite, sulfur-doped silicon-oxygen material and sulfur-doped silicon-carbon material.
[0008] As an optional embodiment, the carbonate-based compound includes at least one of vinylene carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0009] As an optional embodiment, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, and lithium difluorooxalatoborate; and / or
[0010] In the electrolyte, the molar concentration of the lithium salt is 0.5 mol / L to 10 mol / L.
[0011] As an optional embodiment, the negative electrode active material layer further includes a conductive agent and a binder; and / or
[0012] The conductive agent includes at least one of conductive carbon black super P, conductive carbon black Ketjen black, conductive carbon black acetylene black, conductive carbon black graphite flakes, and carbon nanotubes; and / or
[0013] The binder includes at least one of sodium hydroxymethyl cellulose, sodium alginate, polyacrylic acid, styrene-butadiene rubber, and polyolefin; and / or
[0014] The negative electrode current collector includes copper foil or composite copper foil.
[0015] As an optional embodiment, the battery further includes a counter electrode or a positive electrode plate; and / or
[0016] The counter electrode is a lithium metal sheet; and / or
[0017] The positive electrode sheet comprises a positive electrode active material layer and a positive electrode current collector; and / or
[0018] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a layered oxide, lithium iron phosphate, and lithium manganese iron phosphate; and / or
[0019] The positive electrode current collector comprises aluminum foil or composite aluminum foil;
[0020] The battery further comprises a separator, wherein the separator comprises a polyolefin film, a glass fiber separator and a coating separator; and / or,
[0021] The polyolefin film is selected from one of a polypropylene single-layer film, a polyethylene single-layer film or a polypropylene / polyethylene / polypropylene three-layer composite film; and / or
[0022] The coating material of the coating membrane includes at least one of PVDF, alumina, boehmite, and a solid electrolyte.
[0023] In a second aspect, the present application provides a method for preparing a battery, the method comprising:
[0024] obtaining a sulfur-doped active material;
[0025] coating the sulfur-doped active material as the negative electrode active material on the negative electrode current collector to obtain a negative electrode sheet;
[0026] The negative electrode plate is immersed in an electrolyte containing a carbonate-based compound and a lithium salt to obtain a battery.
[0027] As an optional embodiment, obtaining the sulfur-doped active material includes:
[0028] Using active materials as carriers, the sulfur is sublimated by a steam-melting method and loaded into the pores of the carrier to obtain sulfur-doped active materials.
[0029] In a third aspect, the present application provides an electrical device, the electrical device comprising the battery provided in the first aspect.
[0030] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0031] The battery provided in the embodiment of the present application adopts a sulfur-doped active material as the negative electrode active material, and is matched with an electrolyte containing a carbonate-based compound. By utilizing the common reaction of the carbonate-based compound with lithium polysulfide, an intermediate product of the sulfur conversion reaction, and a lithium salt in the electrolyte, a layer of solid electrolyte-electrode interface with high ionic conductivity and low interface resistance is in situ polymerized on the negative electrode surface during the first week of charging, so that the battery has high safety performance while taking into account good rate performance and electrode-electrolyte interface contact. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0034] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0037] An embodiment of the present application provides a battery, which includes a negative electrode plate and an electrolyte, wherein the negative electrode plate is at least partially immersed in the electrolyte; the negative electrode plate includes a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer is attached to the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a sulfur-doped active material; the electrolyte includes a carbonate-based compound and a lithium salt.
[0038] The battery uses sulfur-doped active materials as negative electrode active materials, and is paired with an electrolyte containing carbonate-based compounds. It utilizes the joint reaction of carbonate-based compounds with lithium polysulfide, an intermediate product of the sulfur conversion reaction, and lithium salts in the electrolyte. During the first week of charging, a layer of solid electrolyte-electrode interface with high ionic conductivity and low interface resistance is in situ polymerized on the negative electrode surface. This allows the battery to have high safety performance while also having good rate performance and electrode-electrolyte interface contact.
[0039] Moreover, this method not only solves the problems of poor electrode-electrolyte interface contact, large interface resistance, and poor battery rate performance formed by non-in-situ methods, but also avoids the impact of residual polymerized monomers / initiators on the battery system. In the embodiment of the present application, the polymerized monomer is the original solvent / additive of the liquid electrolyte, the initiator is the reaction intermediate product of the doped elemental sulfur, and the lithium salt also participates in the reaction.
[0040] In some embodiments, the sulfur-loaded amount of the sulfur-doped active material is 1% to 20% by mass.
[0041] Exemplarily, the sulfur loading of the sulfur-doped active material can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., measured by mass fraction, and it can also be any value in the range of 1% to 20%.
[0042] In some embodiments, the sulfur-doped active material includes at least one of sulfur-doped graphite, sulfur-doped silicon-oxygen material, and sulfur-doped silicon-carbon material.
[0043] In some embodiments, the carbonate-based compound includes one or more combinations of vinylene carbonate (VC), fluoroethylene carbonate (FEC), propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC),
[0044] In some embodiments, the lithium salt includes a combination of one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorophosphate (LiPO2F2), and lithium difluorooxalatoborate (LiDFOB).
[0045] Furthermore, the molar concentration of the lithium salt is 0.5 mol / L to 10 mol / L.
[0046] Exemplarily, the molar concentration of the lithium salt can be 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L, 5mol / L, 5.5mol / L, 6mol / L, 6.5mol / L, 7mol / L, 7.5mol / L, 8mol / L, 8.5mol / L, 9mol / L, 9.5mol / L or 10mol / L, etc., and it can also be any value in the range of 0.5mol / L to 10mol / L.
[0047] In some embodiments, the negative electrode active material layer further includes a conductive agent and a binder. The conductive agent includes conductive carbon black, and the conductive carbon black is selected from one or more of conductive carbon black super P, conductive carbon black Ketjen black, conductive carbon black acetylene black, conductive carbon black graphite flakes, and carbon nanotubes. The binder includes at least one of sodium carboxymethylcellulose (CMC), sodium alginate (SA), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and polyolefin.
[0048] In some embodiments, the negative electrode current collector includes copper foil or composite copper foil (ie, composite current collector).
[0049] In some embodiments, the battery further comprises a positive electrode sheet, which may be a metal lithium sheet or a positive electrode sheet composed of a positive current collector and a positive electrode active material layer. The positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises at least one of a layered oxide, lithium iron phosphate, and lithium manganese iron phosphate.
[0050] In some embodiments, the battery further comprises a separator. The separator is selected from a polyolefin film, a glass fiber separator and a coating separator; the polyolefin film is selected from a polypropylene monolayer film (PP), a polyethylene monolayer film (PE) and a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP); the coating separator is selected from a PE base film coated with PVDF, alumina, boehmite, and a solid electrolyte.
[0051] In some embodiments, the battery may be a semi-solid battery, and the semi-solid lithium battery includes a button battery, a soft-pack battery, a square aluminum shell battery, and a cylindrical battery.
[0052] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, based on a general inventive concept, an embodiment of the present application also provides a method for preparing a battery.
[0053] The method is used for preparing the above-mentioned battery. The specific content of the battery can refer to the above-mentioned embodiment. Since the method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0054] In some embodiments, the method comprises:
[0055] S1. Obtaining sulfur-doped active material;
[0056] In some embodiments, obtaining the sulfur-doped active material includes: using the active material as a carrier, sublimating sulfur by a steam-melt method, and loading the sulfur into the pores of the carrier to obtain the sulfur-doped active material.
[0057] Specifically, in this embodiment, graphite, silicon-oxygen material or silicon-carbon material is used as a carrier, and a sulfur-doped negative electrode active material is obtained by a steam-melt method or by loading a certain proportion of sublimated sulfur into its pores; that is, the carrier and sulfur powder are mixed and ground and then vacuum-sealed, first heated at 350°C for 6h, then cooled to 155°C and maintained for 6h, and then cooled to room temperature to obtain a sulfur-doped negative electrode active material.
[0058] The carrier can be specifically selected from one or more combinations of natural graphite, artificial graphite, porous silicon oxygen, and porous silicon carbon.
[0059] S2. The sulfur-doped active material is applied to the negative electrode current collector as the negative electrode active material to obtain a negative electrode sheet;
[0060] Specifically, in this embodiment, the sulfur-doped active material is mixed with conductive carbon black and a binder to obtain a negative electrode slurry, the negative electrode slurry is coated on a current collector, and vacuum dried to obtain a negative electrode sheet.
[0061] S3. Immerse the negative electrode plate in an electrolyte containing a carbonate-based compound and a lithium salt to obtain a battery.
[0062] Specifically, in this embodiment, under a protective atmosphere, a negative electrode plate and a metal lithium plate or a positive electrode plate made of a lithium-containing material such as a layered oxide / lithium iron phosphate / lithium manganese iron phosphate, a separator and an electrolyte are assembled into a lithium battery. The preparation of the electrolyte includes dissolving a lithium salt in a carbonate-based solvent to obtain an electrolyte with a lithium salt concentration of 0.5 to 10 mol / L.
[0063] Based on a general inventive concept, an embodiment of the present application further provides an electrical device, which includes the battery provided above.
[0064] The electrical equipment is implemented based on the above-mentioned battery. The specific content of the battery can refer to the above-mentioned embodiment. Since the electrical equipment adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.
[0065] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0066] Example 1
[0067] A semi-solid lithium battery, the preparation method thereof has the following specific steps:
[0068] Step 1): Weigh the corresponding mass ratio of commercial artificial graphite and sulfur powder in a mortar, grind them evenly, transfer them to a glass tube, evacuate and seal them. Then place it in a muffle furnace and heat it at 350°C for 6 hours, then cool it to 155°C and keep it for 6 hours, and finally cool it to room temperature to obtain a composite negative electrode material with a sulfur loading of 5wt%.
[0069] Step 2): The composite negative electrode material obtained in step 1) is uniformly mixed with conductive carbon black (super P) and a binder (PAA) in a mass ratio of 8:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80° C. and dried for 12 h to obtain a negative electrode sheet.
[0070] Step 3): Use the electrode sheet obtained above as the negative electrode, the metal lithium sheet as the counter electrode, the polypropylene film as the separator, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte to assemble into a CR2032 button cell in a glove box filled with argon.
[0071] Example 2
[0072] A semi-solid lithium battery, the preparation method thereof has the following specific steps:
[0073] Step 1): Weigh the corresponding mass ratio of commercial porous silicon carbon and sulfur powder, grind them evenly in a mortar, transfer them to a glass tube, evacuate and seal them. Then place it in a muffle furnace and heat it at 350°C for 6 hours, then cool it to 155°C for 6 hours, and finally cool it to room temperature to obtain a composite negative electrode material with a sulfur loading of 5wt%.
[0074] Step 2): The composite negative electrode material obtained in step 1) is uniformly mixed with conductive carbon black (super P) and a binder (PAA) in a mass ratio of 8:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80° C. and dried for 12 h to obtain a negative electrode sheet.
[0075] Step 3): Use the electrode sheet obtained above as the negative electrode, the metal lithium sheet as the counter electrode, the polypropylene film as the separator, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte to assemble into a CR2032 button cell in a glove box filled with argon.
[0076] Example 3
[0077] A semi-solid lithium battery, the preparation method thereof has the following specific steps:
[0078] Step 1): Weigh commercial artificial graphite and porous silicon carbon with a mass ratio of 3:1, and sulfur powder, grind them evenly in a mortar, transfer them to a glass tube, evacuate and seal them. Then place it in a muffle furnace and heat it at 350°C for 6 hours, then cool it to 155°C for 6 hours, and finally cool it to room temperature to obtain a composite negative electrode material with a sulfur loading of 5wt%.
[0079] Step 2): The composite negative electrode material obtained in step 1) is uniformly mixed with conductive carbon black (super P) and a binder (PAA) in a mass ratio of 8:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80° C. and dried for 12 h to obtain a negative electrode sheet.
[0080] Step 3): Use the electrode sheet obtained above as the negative electrode, the metal lithium sheet as the counter electrode, the polypropylene film as the separator, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte to assemble into a CR2032 button cell in a glove box filled with argon.
[0081] Example 4
[0082] A semi-solid lithium battery, the preparation method thereof has the following specific steps:
[0083] Step 1): Weigh commercial artificial graphite and porous silicon carbon with a mass ratio of 3:1, and sulfur powder, grind them evenly in a mortar, transfer them to a glass tube, evacuate and seal them. Then place it in a muffle furnace and heat it at 350°C for 6 hours, then cool it to 155°C for 6 hours, and finally cool it to room temperature to obtain a composite negative electrode material with a sulfur loading of 10wt%.
[0084] Step 2): The composite negative electrode material obtained in step 1) is uniformly mixed with conductive carbon black (super P) and a binder (PAA) in a mass ratio of 8:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80° C. and dried for 12 h to obtain a negative electrode sheet.
[0085] Step 3): Use the electrode sheet obtained above as the negative electrode, the metal lithium sheet as the counter electrode, the polypropylene film as the separator, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte to assemble into a CR2032 button cell in a glove box filled with argon.
[0086] Example 5
[0087] A semi-solid lithium battery, the preparation method thereof has the following specific steps:
[0088] Step 1): Weigh commercial artificial graphite and porous silicon carbon with a mass ratio of 3:1, and sulfur powder, grind them evenly in a mortar, transfer them to a glass tube, evacuate and seal them. Then place it in a muffle furnace and heat it at 350°C for 6 hours, then cool it to 155°C for 6 hours, and finally cool it to room temperature to obtain a composite negative electrode material with a sulfur loading of 5wt%.
[0089] Step 2): The composite negative electrode material obtained in step 1) is uniformly mixed with conductive carbon black (super P) and a binder (PAA) in a mass ratio of 8:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80° C. and dried for 12 h to obtain a negative electrode sheet.
[0090] Step 3): Use the electrode sheet obtained above as the negative electrode, commercial NCM811 as the positive electrode, a commercial coated diaphragm as the diaphragm, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte to assemble a small soft-pack battery in an environmentally controlled soft-pack line.
[0091] Comparative Example 1
[0092] A liquid lithium battery, the preparation method thereof has the following specific steps:
[0093] Step 1): Commercial artificial graphite, conductive carbon black (super P) and binder (PAA) are uniformly mixed in a mass ratio of 8:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80°C for 12 hours to obtain a negative electrode sheet.
[0094] Step 2): Using the electrode sheet obtained above as the negative electrode, the metal lithium sheet as the counter electrode, the polypropylene film as the separator, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte, assemble into a CR2032 button cell in a glove box filled with argon.
[0095] Comparative Example 2
[0096] A liquid lithium battery, the preparation method thereof has the following specific steps:
[0097] Step 1): Commercial porous silicon carbon, conductive carbon black (super P) and binder (PAA) are uniformly mixed in a mass ratio of 8:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80°C for 12 hours to obtain a negative electrode sheet.
[0098] Step 2): Using the electrode sheet obtained above as the negative electrode, the metal lithium sheet as the counter electrode, the polypropylene film as the separator, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte, assemble into a CR2032 button cell in a glove box filled with argon.
[0099] Comparative Example 3
[0100] A liquid lithium battery, the preparation method thereof has the following specific steps:
[0101] Step 1): Commercial artificial graphite, porous silicon carbon, conductive carbon black (super P) and binder (PAA) are uniformly mixed in a mass ratio of 6:2:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80°C for 12 hours to obtain a negative electrode sheet.
[0102] Step 2): Using the electrode sheet obtained above as the negative electrode, the metal lithium sheet as the counter electrode, the polypropylene film as the separator, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte, assemble into a CR2032 button cell in a glove box filled with argon.
[0103] Comparative Example 4
[0104] A liquid lithium battery, the preparation method thereof has the following specific steps:
[0105] Step 1): Commercial artificial graphite, porous silicon carbon, conductive carbon black (super P) and binder (PAA) are uniformly mixed in a mass ratio of 6:2:1:1 to obtain a slurry, and then the slurry is coated on a current collector copper foil, and placed in a vacuum drying oven at 80°C for 12 hours to obtain a negative electrode sheet.
[0106] Step 2): Use the electrode sheet obtained above as the negative electrode, commercial NCM811 as the positive electrode, a commercial coated diaphragm as the diaphragm, and a solution containing lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) as the electrolyte to assemble a small soft-pack battery in an environmentally controlled soft-pack line.
[0107] The battery prepared in Example 5 was subjected to needle puncture and hot box tests and compared with the battery prepared in Comparative Example 4. The results are shown in the following table.
[0108] Group Pass or fail the acupuncture test 150℃ hot box passed or not Example 5 yes yes Comparative Example 4 no no
[0109] It can be seen from the above table that the semi-solid lithium battery assembled with the sulfur-doped composite negative electrode can pass the needle puncture test and the 150°C hot box, while the liquid lithium battery without sulfur cannot pass.
[0110] For Examples 1 to 5, the prepared batteries were subjected to rate charge and discharge tests at a current density of 2C, and the capacity retention rate after 50 cycles was recorded and compared with the batteries of Comparative Examples 1 to 4. The results are shown in the following table.
[0111]
[0112]
[0113] It can be seen from the above table that the rate performance of the battery assembled using the sulfur-doped composite negative electrode is significantly improved compared to that of the sulfur-free one.
[0114] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0115] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.
[0116] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A battery, characterized in that: The battery comprises a negative electrode plate and an electrolyte, wherein the negative electrode plate is at least partially immersed in the electrolyte; the negative electrode plate comprises a negative electrode active material layer and a negative electrode current collector, wherein the negative electrode active material layer is attached to the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, wherein the negative electrode active material comprises a sulfur-doped active material; and the electrolyte comprises a carbonate-based compound and a lithium salt.
2. The battery according to claim 1, characterized in that Calculated by mass fraction, the sulfur-loaded content of the sulfur-doped active material is 1% to 20%.
3. The battery according to claim 1, characterized in that The sulfur-doped active material includes at least one of sulfur-doped graphite, sulfur-doped silicon-oxygen material and sulfur-doped silicon-carbon material.
4. The battery according to claim 1, characterized in that The carbonate-based compound includes at least one of vinylene carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate.
5. The battery according to claim 1, characterized in that The lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, and lithium difluorooxalatoborate; and / or In the electrolyte, the molar concentration of the lithium salt is 0.5 mol / L to 10 mol / L.
6. The battery according to claim 1, characterized in that The negative electrode active material layer further includes a conductive agent and a binder; and / or The conductive agent comprises conductive carbon black; and / or The binder comprises at least one of sodium hydroxymethyl cellulose, sodium alginate, polyacrylic acid, styrene-butadiene rubber and polyolefin; and / or The negative electrode current collector includes copper foil or composite copper foil.
7. The battery according to claim 1, characterized in that The battery further comprises a counter electrode or a positive electrode sheet; and / or The counter electrode is a metal lithium sheet; and / or The positive electrode sheet comprises a positive electrode active material layer and a positive electrode current collector; and / or The positive electrode active material layer includes a positive electrode active material, wherein the positive electrode active material includes at least one of a layered oxide, lithium iron phosphate and lithium manganese iron phosphate; and / or The positive electrode current collector comprises aluminum foil or composite aluminum foil; and / or The battery further comprises a separator, wherein the separator comprises a polyolefin film, a glass fiber separator and a coating separator; and / or The polyolefin film is selected from one of a polypropylene single-layer film, a polyethylene single-layer film or a polypropylene / polyethylene / polypropylene three-layer composite film; and / or The coating material of the coating membrane includes at least one of PVDF, alumina, boehmite, and a solid electrolyte.
8. A method for preparing a battery, characterized in that: The method comprises: obtaining a sulfur-doped active material; coating the sulfur-doped active material as a negative electrode active material on a negative electrode current collector to obtain a negative electrode sheet; The negative electrode plate is immersed in an electrolyte containing a carbonate-based compound and a lithium salt to obtain a battery.
9. The method for preparing a battery according to claim 8, characterized in that: The obtaining of the sulfur-doped active material comprises: Using the active material as a carrier, subliming sulfur by a steam-melt method, and loading the sulfur into the pores of the carrier to obtain a sulfur-doped active material; and / or The carrier includes at least one of a graphite material, a silicon-oxygen material and a silicon-carbon material.
10. An electrical device, characterized in that: The electrical device comprises the battery according to any one of claims 1 to 7.
Citation Information
Patent Citations
Sulfur-carbon composite and lithium-sulfur battery including same
CN111357136A
Semi-solid lithium-sulfur battery and preparation method thereof
CN114765272A
Construction method and application of stable interface of sulfur positive electrode material of lithium-sulfur battery
CN116344945A
Secondary battery and device
CN116417570A
Secondary battery and device
CN116435602A
